2014
DOI: 10.1007/s00167-014-2988-3
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of suture–tendon interface and tissue holding of three suture configurations in torn and degenerated versus intact human rotator cuffs

Abstract: Clinicians better use repair techniques that grasp greater tissue volume (e.g. MCS, modified Mason-Allen cross bridge, double-row cross bridge, etc.) when repairing the torn and degenerated rotator cuffs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…63 Similarly, cell apoptosis is seen throughout degenerated tendon, 64,65 with concurrent elevations in inflammatory and catabolic mediators. 66,67 These degenerative changes not only weaken the suture retention strength, thereby predisposing to surgical failure, 18 but also impair healing. Namely, it was recently reported that the severity of tendinosis, rather than tear size or fatty infiltration, was the greatest predictor of repair integrity at least 6 months after surgery.…”
Section: Mechanical Augmentation Of the Surgical Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…63 Similarly, cell apoptosis is seen throughout degenerated tendon, 64,65 with concurrent elevations in inflammatory and catabolic mediators. 66,67 These degenerative changes not only weaken the suture retention strength, thereby predisposing to surgical failure, 18 but also impair healing. Namely, it was recently reported that the severity of tendinosis, rather than tear size or fatty infiltration, was the greatest predictor of repair integrity at least 6 months after surgery.…”
Section: Mechanical Augmentation Of the Surgical Repairmentioning
confidence: 99%
“…1). 18 Novel surgical techniques have been developed in an effort to improve footprint coverage and reduce shear stresses at the suture-tendon interface, theoretically enhancing healing at the interface and reducing repair failure. 19,20 While these techniques have shown promise in studies with cadaveric specimens, clinical studies have not consistently found improvements in structural healing or functional outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The suture–tendon/ligament interface was identified as the critical limit to successful tendon/ligament repair. 41 High friction between sutures and tissues may cause pain and inflammation, then lead to a longer healing time. An ideal suture should have minimal suture-to-tissue friction force.…”
Section: Discussionmentioning
confidence: 99%
“…A custom-made software program on a personal computer was used to control the desired force, the cycle speed, and the number of cycles. First, each model was subjected to a 5 N preload and a cyclic load of 5-30 N at 0.6 mm/s for 20 cycles (Ma et al, 2004;Mihata et al, 2011;Wlk et al, 2015). The tendon model was then subjected to simple tensile loading at 0.6 mm/s until reaching failure (Millett et al, 2017).…”
Section: Biomechanical Testingmentioning
confidence: 99%